ANALISIS RENDAHNYA MINAT BELAJAR MATEMATIKA PADA PESERTA DIDIK KELAS III SD NEGERI DUMELING 01 - Izzatul Mar'ah; Tri Setiyoko, Didik; Yuliyanti, Novi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The research was conducted to identify the various problems encountered in mathematics learning among elementary school students. The type of research used is qualitative descriptive, where in this research the researcher describes the activities observed in the field with specific, in-depth and transparent characteristics. Primary data were obtained directly from interviews and information gathered from research subjects, namely the third-grade teacher and students at SD Negeri Dumeling 01. Secondary data were collected from journals, notes, library books, and previous studies to support and strengthen the primary data obtained at the school. Based on the findings, it can be concluded that the challenges in teaching mathematics, particularly in multiplication and division material for third-grade students, stem from a combination of internal factors such as students’ learning styles and interest, and external factors such as family support, lack of variation in teaching methods, and a classroom environment that does not yet fully support effective learning. Therefore, a more creative, contextual, and enjoyable teaching approach is needed, along with active support from families, to foster students’ interest in learning from an early age.